Child-Parent Relationship Therapy for Externalizing Problems: A Meta-analysis and Methodological Critique. Issue 4 (1st October 2020) - Allen, Brian
ABSTRACT: Child-Parent Relationship Therapy (CPRT) is a parent-training program derived from the filial therapy traditional that has been previously described as an efficacious treatment for children with externalizing problems (e.g., aggression, defiance). The current paper describes the results of a meta-analysis of CPRT for purposes of determining the impact CPRT may have on such problems using effect sizes based on parent-report measures. A total of 23 studies ( n = 333) were identified that either examined pre- to post-treatment change or compared CPRT to a waitlist control condition. Results suggested that CPRT tends to obtain medium-sized effects when examining pre-post change ( g =.554) as well as medium effects when compared to a waitlist condition ( g =.59). Analyses suggested relatively little variability across studies, and thus potential moderators of effect (e.g., outcome measure utilized, modifications of intervention delivery, participant characteristics) did not impact outcomes. However, these effects were smaller than those typically observed among other parent training programs in general and multiple methodological concerns limit the interpretability of these findings, notably that nearly all studies included participants whose children did not display significant behavioral problems. A methodological critique of the CPRT literature discusses multiple identified limitations, including recommendations for how to improve these studies.